Deposit policy of a commercial bank and fund raising operations - Xiao Yue (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the deposit policy and fund-raising operations of the commercial bank JSC "Oschadbank". The subject of research is the financial relations that arise between a commercial bank and its clients in the context of conducting a deposit policy. The purpose of the qualifying master's thesis is to provide a comprehensive assessment of the state of the deposit policy of a commercial bank and to determine the main directions for its improvement. Based on the results of the research, theoretical and practical provisions were formulated and translated into concrete proposals aimed at improving the state of the deposit policy. The study identified key weaknesses and challenges within the current deposit policy of JSC "Oschadbank," including gaps in liability management and risk mitigation strategies. It also highlighted innovative trends in deposit product offerings that could enhance the bank's competitiveness in the market.
Депозитна політика комерційного банку і операції по залученню коштів
Scientific adviser: Utenkova Karina, doctor of economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; deposits; interest on deposits; deposit policy; liabilities of the bank; banking risks; innovations